Sistem Informasi Penjualan Sayur Berbasis Website Menggunakan Framework Codeigniter - Imam Wahyudi; Marini Styawati; Amara Yulia; Riyan Abdul Aziz (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
. Rapid technological developments as well as increasing high economic growth are very influential in the use of technology in a business. existing technological developments to help businesses become better. As in the Fresh Vegetable Shop, which began to apply technology to the use of web-based applications to make buying and selling transactions of fresh fruit and vegetables, which can be done digitally using a smartphone and to make it easier for fruit and vegetable lovers (vegetarians) to get the fruits and vegetables they like. and immediately delivered to the destination so that it can be enjoyed immediately.